2021
DOI: 10.1038/s41467-021-24230-5
|View full text |Cite|
|
Sign up to set email alerts
|

Twelve-month specific IgG response to SARS-CoV-2 receptor-binding domain among COVID-19 convalescent plasma donors in Wuhan

Abstract: To investigate the duration of humoral immune response in convalescent coronavirus disease 2019 (COVID-19) patients, we conduct a 12-month longitudinal study through collecting a total of 1,782 plasma samples from 869 convalescent plasma donors in Wuhan, China and test specific antibody responses. The results show that positive rate of IgG antibody against receptor-binding domain of spike protein (RBD-IgG) to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in the COVID-19 convalescent plasma donor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
50
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 32 publications
8
50
1
Order By: Relevance
“…When we compared anti-S IgG levels at M10 with those at M2, we found them to be reduced in 16 subjects and upregulated in 12 (Figure 4E-G). Interestingly, we found that those who had increased anti-S IgG levels at M10 were older when compared to those who displayed decreased anti-S IgG levels at M10 (p = 0.01), as already reported in a series of studies conducted in healthy subjects [17][18][19]. Next, using the mathematical modeling approach developed by Miles P. Davenport and co-workers, which provides a quantitative prediction of the link between neutralizing antibody levels and clinical protection, we estimated the 50% protective neutralization level against SARS-CoV-2 infection in our cohort to be 78.338 in the M2 group, calculated as 20.2% of the mean level [20].…”
Section: Comparative Analysis Of the Igg Titers And The Neutralizing Response At Ten Months After The First Positive Pcr Test (M10)supporting
confidence: 86%
See 2 more Smart Citations
“…When we compared anti-S IgG levels at M10 with those at M2, we found them to be reduced in 16 subjects and upregulated in 12 (Figure 4E-G). Interestingly, we found that those who had increased anti-S IgG levels at M10 were older when compared to those who displayed decreased anti-S IgG levels at M10 (p = 0.01), as already reported in a series of studies conducted in healthy subjects [17][18][19]. Next, using the mathematical modeling approach developed by Miles P. Davenport and co-workers, which provides a quantitative prediction of the link between neutralizing antibody levels and clinical protection, we estimated the 50% protective neutralization level against SARS-CoV-2 infection in our cohort to be 78.338 in the M2 group, calculated as 20.2% of the mean level [20].…”
Section: Comparative Analysis Of the Igg Titers And The Neutralizing Response At Ten Months After The First Positive Pcr Test (M10)supporting
confidence: 86%
“…Both anti-RBD and anti-S antibody levels were below the detection limit of the assays in 7% of the subjects after ~50 days from the first SARS-CoV-2 positive PCR test, indicating that these patients did not seroconvert or had already lost their seroconversion at this time point [5,19,21]. At this time point, both anti-RBD and anti-S IgG levels were significantly higher in hospitalized subjects than those observed in asymptomatic or symptomatic patients.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…A recent 12-month longitudinal study was published with 1,782 plasma samples from 869 convalescent plasma donors in Wuhan, China. This study has shown that among COVID-19 plasma donors the positive rate of IgG antibody against the SARS-CoV-2 receptor binding domain (RBD) in the spike protein exceeded 70% for 12 months post-diagnosis(C. Li et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Following recovery of COVID-19 patients, specific IgG antibodies can last for at least 12 months in 70-90% of the convalescent COVID-19 patients who showed severe symptoms and were hospitalized [101][102][103][104][105]. The IgG titers remain in higher titers within the first 6 months of convalescence and maintain stability for the following second 6 months [101][102][103]. In mild-to-moderate patients, the IgG titers persist relatively high titers for more than 6 months after recovery [104].…”
Section: Immune Response To Coronavirus Infectionmentioning
confidence: 99%